Possibilities of distance learning techniques of computer graphics - Кулдыбаев, Айбек; Нуралин, А.; Сагиров, А. (Pedagogy and Psychology, 2022)
Today, within the framework of educational programs, there are a large number of opportunities to create unique directions for combining the accumulated pedagogical experience and training standards. It is important to take into account not only the current standards and provisions of the educational program, but also the process of possible application of innovative digital and information technologies. Within the framework of the current restrictions related to the spread of coronavirus infection, the relevance of the use of distance learning is increasing. The presence of various kinds of electronic learning materials helps to ensure the implementation of distance learning. They include not only a training complex, but also some test tasks that help to implement self-control of knowledge. Distance learning with the use of modern means of transmitting information, broadcasting it to students in real time, today helps to form some initial skills, develop them in the process of fruitful interaction with the teacher.